Estimation of the burden of disease averted by leisure center membership across Spain - Jimenez, Alfonso; Nieto, Inés; Mayo, Xian; Bascones, Pablo; De Soto Cardenal, Jesús; Arroyo, Alfonso; Liguori, Gary; Davies, Larissa (Frontiers in Sports and Active Living, 2025)
IntroductionActive behavior performed in leisure centers might help reduce the negative health impacts associated with physical inactivity. The disability-adjusted life years (DALYs) is a valuation technique to quantify lifetime disease burden including both non-fatal health consequences of diseases and premature death.MethodThis study estimated the role of the largest leisure center in Spain (GO fit) in averting the burden of five diseases and premature deaths during 2017 as a consequence of the physical activity and exercise programs and services delivered. A preferred model was implemented with a static picture of the burden of disease, without including discounting rate and age-weights. Sensitivity analyses were conducted considering these two variables.ResultsThe estimation was that GO fit services could have averted a total of 1,165.74 DALYs (10.96 DALYs per 1,000 members) coming from type 2 diabetes (22.62 DALYs), colorectal cancer (81.16 DALYs), breast cancer (48.72 DALYs), stroke (206.15 DALYs), and coronary heart disease (807.10 DALYs).DiscussionThese results indicate that programs and services delivered in physical activity leisure centers could help the public health agenda aim of promoting a more active lifestyle and reducing the burden of disease associated with physical inactivity.